LEARNING OBSTACLE : SISWA MTs. KELAS VIII DALAM MENYELESAIKAN SOAL MATERI BARISAN DAN DERET ARITMATIKA BERDASARKAN LEVEL KOGNITIF HOTS - Lusiana Tika Syafitri; Nelly Fitriani; Puji Nurfauziah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to further examine learning obstacles: MTs.class VIII students in solving arithmetic sequence and series material problems based on the cognitive level of HOTS (High-Order Thinking Skills) with the aim of analyzing and describing the location of errors experienced by students in completing material problems in the Rows and Arithmetic Series material. In this study, the method used was descriptive qualitative. The subjects in this study were MTs. class VIII students in Cikembang, Bandung Regency for the 2021-2022 academic year. The data collection technique was carried out by providing 5 questions of the description test with the criteria of the HOTS cognitive level. With the indicators used are (1) Finding the nth term of the arithmetic row of an already given row (C4). (2) Create the nth pattern and tribe of an arithmetic series (C6). (3) Comparing the differences and nth tribes on the arithmetic sequence (C5). Based on the results of the analysis, it is stated that there are some difficulties for students when solving arithmetic rows and series questions on the indicator of question number 2 is relatively high, namely the indicator Making patterns and nth tribes of an arithmetic series with an error percentage of 85%. Furthermore, question number 4 shows the indicator Solving contextual problems related to the nth term of the arithmetic sequence with an error percentage of 75%.